Use of hemostatic agents for surgical bleeding in laparoscopic partial nephrectomy: Biomaterials perspective. Issue 8 (26th May 2020) - Pacheco, Margarida; Barros, Alexandre A.; Aroso, Ivo M.; Autorino, Riccardo; Lima, Estêvão; Silva, Joana M.; Reis, Rui L.
Abstract: In recent years, there was an abrupt increase in the incidence of renal tumors, which prompt up the appearance of cutting‐edge technology, including minimally invasive and organ‐preserving approaches, such as laparoscopic partial nephrectomy (LPN). LPN is an innovative technique used to treat small renal masses that have been gaining popularity in the last few decades due to its promissory results. However, the bleeding control remains the main challenge since the majority of currently available hemostatic agents (HAs) used in other surgical specialities are inefficient in LPN. This hurried the search for effective HAs adapted for LPN surgical peculiarities, which resulted on the emergence of different types of topical HAs. The most promising are the natural origin HAs because of their inherent biodegradability, biocompatibility, and lowest toxicity. These properties turn them top interests' candidates as HAs in LPN. In this review, we present a deep overview on the progress achieved in the design of HAs based on natural origin polymers, highlighting their distinguishable characteristics and providing a clear understanding of their hemostat's role in LPN. This way it may be possible to establish a structure–composition properties relation, so that novel HAs for LPN can be designed to explore current unmet medical needs.